Sensitivity assessment and simulation of ecosystem services in response to land use change in arid regions: Empirical evidence from Xinjiang, China - Xiaoyun Li; Chunsheng Wu (Ecological Indicators)
Ecosystem services are essential for human life, but they have undergone significant degradation in recent decades, mainly due to human-induced land use change. This research focuses on Xinjiang, the largest and most typical arid region in China, where ecosystem services are particularly sensitive to land use change. An improved framework for assessing and simulating ecosystem services combining a modified equivalent factor method, a future land use simulation (FLUS) model, and a cross-sensitivity analysis is proposed. The main results are obtained as follows: (1) During 1980 and 2020, construction land and cultivated land expanded by 115.66% and 47.18%, respectively, primarily owing to intensive socio-economic activities. The expense was the losses of forest land and grassland, with reductions of 5.84% and 4.15%, respectively. Besides, the water body expanded slightly, primarily owing to climate change. (2) The total ecosystem service value (ESV), despite a 3.2% rise during the research period, exhibited a fluctuating pattern as a result of frequent changes in land use. Given the current development momentum, the total ESV will present a downward trend by 2030 according to the simulation. (3) The ESV change revealed a notable spatial difference, wherein the loss of ESV was concentrated primarily in two major economic belts, while the rise was primarily observed in areas where the natural ecosystem and biological diversity were effectively protected. (4) The cross-sensitivity analysis demonstrated an extremely high sensitivity of ESV towards the change in water body and a relatively low sensitivity towards the change in construction land and cultivated land. (5) Enhancing intensive use of construction land, promoting yield and quality of cultivated land, prioritizing developing unused land, and strengthening water conservation are crucial for ecologically fragile arid regions. This research will enhance our understanding of the human-environment interaction in arid regions and ultimately support their sustainable development from the perspective of effective land use management.